PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KOPI BUBUK INSTANT NESCAFE DI BATAM - Kheren Kheren; Inda Sukati (LPPM Universitas Putera Batam, 2026)
This research aims to examine the influence of brand image, product quality, and promotion on purchase decisions of Nescafe instant coffee in Batam City. This study uses a quantitative research method. The research sample consisted of 120 respondents who have consumed Nescafe instant coffee in Batam City. The data collection method used was primary data obtained through questionnaires. Data processing was carried out using the SPSS Version 26 program. Based on the data and analysis that have been conducted, the results show that brand image does not have a significant effect on purchase decisions of Nescafe instant coffee in Batam City. In addition, product quality also does not have a significant effect on purchase decisions. Meanwhile, promotion has a positive and significant influence on purchase decisions of Nescafe instant coffee in Batam City. Simultaneously, brand image, product quality, and promotion have a significant effect on purchase decisions of Nescafe instant coffee in Batam City.